A Comparison of Risperidone and Buspirone for Treatment of Behavior Disorders in Children with Phenylketonuria - FAYYAZI, Afshin; SALARI*, Elham; KHAJEH, Ali; GAJARPOUR, Abdi (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Fayyazi A, Salari E, Khajeh A, Ghajarpour A. A Comparison of Risperidone and Buspirone for Treatment of Behavior Disorders in Children with Phenylketonuria. Iran J Child Neurol. 2014 Autumn; 8(4):33-38. Abstract Objective Many patients with late-diagnosed phenylketonuria (PKU) suffer from severe behavior problems. This study compares the effects of buspirone and risperidone on reducing behavior disorders in these patients. Materials & Methods In this crossover clinical trial study, patients with severe behavior disorders after medical examination were randomly divided into two groups of two 8-week crossover treatments with risperidone or buspirone. Patient behavioral disorders before and after treatment by each drug was rated by parents on the Nisonger Child Behavior Rating Form (NCBRF), and after treatment by each drug, were assessed by a physician through clinical global impression (CGI). Results Thirteen patients were able to complete the therapy period with these two medications. The most common psychiatric diagnoses were intellectual disability accompanied by pervasive developmental disorder NOS, and intellectual disability accompanied by autistic disorder. Risperidone was significantly effective in reducing the NCBRF subscales of hyperactivity disruptive/ stereotypic, and conduct problems. Treatment by buspirone only significantly decreased the severity of hyperactivity, but other behavior aspects showed no significant differences. Assessment of the severity of behavior disorder after treatment by risperidone and buspirone showed significant differences in reducing hyperactivity and masochistic/stereotype. Conclusion Although buspirone is effective in controlling hyperactivity in patients with PKU, it has no preference over risperidone. Therefore, it is recommended as an alternative to risperidone. References Smith I, Nowles JK. Behaviour in early treated phenylketonuria: a systematic review. Eur J Pediatr 2000;159:89-93. Targum SD and Lang W .Neurobehavioral Problems Associated with Phenylketonuria. Psychiatry (Edgemont) 2009; 7(12):29–32. Luciana M, Hanson K L,Whitley C B.A preliminary report on dopamine system reactivity in PKU: acute effects of haloperidol on neuropsychological, physiological, and neuroendocrine functions. Psychopharmacology 2004;175: 18–25. Pappadopulos E, Woolston S, Chait A, Perkins M, Connor DF, Jensen P S. Pharmacotherapy of Aggression in Children and Adolescents: Efficacy and Effect Size. J CDN ACAD Child Adolesc Psychiatry 2006; 15(1):27-39. Shea S, Turgay A, Carroll A, Schulz M, Orlik H ,Smith I and et al. Risperidone in the Treatment of Disruptive Behavioral Symptoms in Children With Autistic and Other Pervasive Developmental Disorders. Pediatrcs 2004; 114:634-641. Miral S, Gencer O, Inal-Emiroglu F.N, Baykara B, Baykara A, Dirik E. Risperidone versus haloperidol in children and adolescents with AD: a randomized, controlled, doubleblind trial. Eur Child Adolesc Psychiatry 2008; 17:1–8. Aman M.G, Hollway J.A, McDougle C.J, Scahill L, Tierney E, McCracken J.T and et al. Cognitive effects of risperidone in children with autism and irritable behavior. J. Child Adolesc. Psychopharmacol 2008; 18:227–236. Pandina G.J, Bossie C.A, Youssef E, Zhu Y, Dunbar F. Risperidone improves behavioral symptoms in children with autism in a randomized, double-blind, placebocontrolled trial. J Autism Dev Disord 2007; 37:367–373. Luby J, Mrakotsky C, Stalets M.M, Belden A, Heffelfinger A, Williams M and et al. Risperidone in preschool children with autistic spectrum disorders: an investigation of safety and efficacy. J. Child Adolesc. Psychopharmacol 2006; 16:575–587. Nagaraj R, Singhi P, Malhi P. Risperidone in children with autism: randomized, placebo controlled, double blind study. J. Child Neurol 2006; 21:450–455. Haas M, Karcher K, Pandina GJ. Treating Disruptive Behavior Disorders with Risperidone: A 1-Year, Open-Label Safety Study in Children and Adolescents. Journal of Child and Adolescent Psychopharmacology 2008;18(4): 337–346. Jensen P, Buitelaar J, Pandina G, Binder C, Haas M. Management of psychiatric disorders in children and adolescents with atypical antipsychotics. Eur Child Adolesc Psychiatry 2007; 16:104–120. Pandina G, Aman M, Findling R. Risperidone in the management of disruptive behavior disorders. J Child Adolesc Psychopharmacol 2006; 16:379–392. Reyes M, Buitelaar J, Toren P, Augustyns I, Eerdekens M. A randomized, double-blind, placebo-controlled study of risperidone maintenance treatment in children and adolescents with disruptive behavior disorders. Am J Psychiatry 2006; 163:402–410. Reyes M, Croonenberghs J, Augustyns I, Eerdekens M. Long-term use of risperidone in children with disruptive behavior disorders and subaverage intelligence: Efficacy, safety, and tolerability. J Child Adolesc Psychopharmacol 2006; 16:260–272. Croonenberghs J, Fegert JM, Findling RL, De Smedt G, Van Dongen S. Risperidone Disruptive Behavior Study Group: Risperidone in children with disruptive behavior disorders and subaverage intelligence: A 1-year, openlabel study of 504 patients. J Am Acad Child Adolesc Psychiatry 2005; 44:64–72. Aman M G, Smedt G D, Derivan A, Lyons B, Findling R L.Double-Blind, Placebo-Controlled Study of Risperidone for the Treatment of Disruptive Behaviors in Children With Subaverage Intelligence. Am J Psychiatry 2002; 159:1337–1346. Snyder R, Turgay A, Aman M, Binder C, Fisman S, Carroll A. Risperidone Conduct Study Group. Effects of risperidone on conduct and disruptive behavior disorders in children with subaverage IQs. J Am Acad Child Adolesc Psychiatry 2002; 41:1026–1036. Gualtieri T. Buspirone for the Behavior problems of patients with Organic Brain Disorders. J Clin Psycopharmacol 1991; 11:280-281. Stanislav S, Fabre T, Crismon L, Childs A. Buspirone’s Efficacy in Organic-Induced Aggression.J Clin Psycopharmacol 1994;14:126-130. Realmuto GM, August GJ, Garfinkel BD. Clinical effect of buspirone in autistic children. J Clin Psychopharmacol 1989; 9(2):122-5. Ratey J, Sovner R, Parks A, Rogentine K. Buspirone treatment of aggression and anxiety in mentally retarded patients: a multiple-baseline, placebo lead-in study. J Clin Psychiatry 1991; 52(4):159-62. Sorensen MJ, Thomsen PH, Bilenberg N. Parent and child acceptability and staff evaluation of K-SADA-PL: a pilot Study. European Child and Adolescent Psychiatry 2007; 16(5): 293-7. Kaufman J, Brimaher B, Bren, D, Rao U, Flynn C, Moreci P and et al. Schedule for affective disorders and Schizophrenia For school –age children – present and lifetime version- (K-SADS-PL): initial reliability and validity date. Journal of the American Academy of Child and Adolescent Psychiatry 1997; 36(7):980-988. Aman MG, Tassé MJ, Rojahn J, and Hammer D: The Nisonger CBRF: a child behavior rating form for children with developmental disabilities. Research in Developmental Disabilities 1996;17:41–57. Tassé MJ, Aman MG, Hammer D, Rojahn J: The Nisonger Child Behavior Rating Form: age and gender effect and norms. Research in Developmental Disabilities 1996; 17:59–75. Norris M, Lecavalier L. Evaluating the validity of the Nisonger Child Behavior Rating Form – Parent Version. Research in Developmental Disabilities 2011; 32:2894– 2900. Guy W. Clinical global impressions. In: ECDEU Assessment Manual for Psychopharmacology. Rockville, MD, National Institute of Mental Health. 1976.Pp.217- 222. National Institute of Mental Health. CGI (Clinic Global Impression) Scale. Psychopharmacology Bull 1985; 21:839-843. Marder S, Hurford IM, van Kammen DP: Second- Generation Antipsychotics: Biological Therapies. Sadock BJ, Sadock VA, Pedro R: Kaplan & Sadock’s Comprehensive Textbook of Psychiatry, 9th Edition. Philadelphia. Lippincott Williams & Wilkins. 2009. P.3220.